2021
DOI: 10.1515/med-2021-0335
|View full text |Cite
|
Sign up to set email alerts
|

Baicalin improves podocyte injury in rats with diabetic nephropathy by inhibiting PI3K/Akt/mTOR signaling pathway

Abstract: Objective To investigate the effect of baicalin on diabetic nephropathy (DN) rats and podocytes and its mechanism. Methods The rat models with DN were established by high-fat and high-sugar diet and intraperitoneal injection of streptozotocin. The fasting blood glucose (FBG) and weight of rats in each group were measured at 0, 1, 2, 3, and 4 weeks. Their biochemical indicators, expression of inflammatory, and antioxidant fact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 30 publications
0
15
0
Order By: Relevance
“…Consistent with our findings, Ou et al revealed that BA attenuated podocyte damage in DN rats partially via the suppression of inflammatory responses and oxidative stress by inactivating the PI3K/Akt/mTOR pathway. 11 As demonstrated by Yang et al, BA might improve renal function and delay disease progression in DN through its anti-inflammatory and anti-oxidative properties. 13 Ma et al reported that BA treatment suppressed inflammation and oxidative stress in DN by inhibiting the MAPK and Nrf2 signaling.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…Consistent with our findings, Ou et al revealed that BA attenuated podocyte damage in DN rats partially via the suppression of inflammatory responses and oxidative stress by inactivating the PI3K/Akt/mTOR pathway. 11 As demonstrated by Yang et al, BA might improve renal function and delay disease progression in DN through its anti-inflammatory and anti-oxidative properties. 13 Ma et al reported that BA treatment suppressed inflammation and oxidative stress in DN by inhibiting the MAPK and Nrf2 signaling.…”
Section: Discussionmentioning
confidence: 95%
“… 9 BA protects against fluoxetine-induced hepatic injury by repressing inflammation and oxidative stress. 10 BA has also been found to alleviate the progression of DN by relieving podocyte injury, 11 diminishing renal fibrosis, 12 and improving renal function. 13 Moreover, BA exerts a renoprotective role in DN by suppressing inflammation and oxidative stress.…”
Section: Introductionmentioning
confidence: 99%
“…It was found that chondrocyte apoptosis decreased, autophagy increased, and the severity of OA was alleviated in mice with mTOR knockout (Zhang et al, 2015). A growing body of evidence shows that Baicalin can regulate PI3K/AKT/mTOR pathway, which can protect podocytes from injury induced by high glucose and activate macrophage autophagy to play an antimycobacterial and anti‐inflammatory role (Ou et al, 2021; Zhang et al, 2017). In this study, we confirmed that Baicalin can promote chondrocyte autophagy by inhibiting the activation of PI3K/AKT/mTOR pathway.…”
Section: Discussionmentioning
confidence: 99%
“…Baicalin ( Figure 2 e) ameliorated diabetic conditions in db/db mice by alleviating oxidative stress and inflammation, and its underlying mechanisms were associated with the activation of the Nrf2-mediated antioxidant signaling pathway and the inhibition of the MAPK-mediated inflammatory signaling pathway [ 166 ]. Baicalin protected podocytes by downregulating the activity of the PI3K/AKT/mammalian target of rapamycin (mTOR) signaling pathway in STZ-induced DN rats [ 159 ]. Baicalin could also alleviate renal injury in STZ-induced DN mice through restoring Klotho expression and inhibiting Klotho hypermethylation to counter TGF-β1 signaling [ 164 ].…”
Section: Flavonoids In Ckdmentioning
confidence: 99%